EFEKTIFITAS PENGGUNAAN LAGU BERBAHASA JERMAN DALAM PEMBELAJARAN KETERAMPILAN MENYIMAK - Viola Angelina, - (2023)
Listening is one of the important aspects in language learning. This skill needs to be regularly practiced as it cannot be mastered on its own. One of the learning media that can be used as a tool in learning listening skills is songs in German. This study aims to investigate: 1) Students' listening skills before using German songs; 2) Students' listening skills after using German songs; 3) Differences in students' listening skills before and after using German songs; 4) The effectiveness of German songs in learning listening skills; and 5) The students' response to the use of German songs in learning listening skills. This study employed the quantitative approach with a Quasi Experiment research method, involving 20 students' as the experimental class and 20 students' as the control class. This study was conducted at SMAN 9 Bandung during the 2022/2023 academic year. The results showed that: 1) Students' listening skills in the experimental class before the experiment is in the average category, while the skills of students' in control class is in the good category; 2) Students' listening skills in the experimental class after the experiment is in the very good category, while the skills of students' in control class is in the good category; 3) There is a significant difference in listening skills between the post-test results of the experimental and control class; 4) The use of German songs is effective in learning listening skills; and 5) The majority of students' agree that the use of German songs makes learning more effective. Based on the results of this study, German songs can be recommended as one of the learning media for German listening skills, as songs have a positive impact on learning listening skills and make students more actively engaged in the learning process. Keywords: listening skill, German songs, learning media